Ocular Lyme borreliosis as a rare presentation of unilateral vision loss. (25th April 2016) - Patterson-Fortin, Jeffrey; Kohli, Anita; Suarez, Maria J; Miller, P Elliott
Abstract : Ocular Lyme borreliosis is a rare manifestation of Lyme disease. We describe a case of an 80-year-old woman who presented with a 1-month history of unilateral painless central vision loss. Based on a temporal artery biopsy, she was initially diagnosed with giant cell arteritis and treated with a 3-day course of high-dose intravenous steroids. A more detailed history uncovered multiple previous treatments for Lyme disease and residence in an endemic Lyme area. The patient was subsequently diagnosed with ocular Lyme borreliosis and treated with intravenous antibiotics. After 5 weeks of treatment, unilateral vision loss did not progress and optic disc oedema resolved.